Great maps - Brotton, Jerry; Smithsonian Institution (London Dorling Kindersley Publishing, 2014)
Traces human development and culture through cartography, from early rock carvings to the latest geospatial technology.
Classical maps 1500 BC-1300 CE -- Discovery and travel 1300-1570 -- New directions and beliefs 1570-1750 -- Thematic maps 1750-1900 -- Modern mapping 1900 to present.
Cover title "Great maps : the world's masterpieces explored and explained."
Includes index.
Keywords: Cartography -- History; Cartography; Maps